Library automation of University of Malaya Library system: the hardware componebt and environment - Lee, A. (University of Malaya Library, 1991)
Digital equipment products form the major hardware component of University of Malaya Library (UML) system computerization programme. The central processing unit (CPU) is a digital VAX6410 mid-range computer. Other digital products are the terminal servers, workstations and storage devices. Third-party products are sourced for multiplexers, modems, printers and bar-code readers. A local area network using an Ethernet communication protocol conncts the various departments in the Main Library. Branch libraries are linked to the Main library via telephone lines with multiplexers and modems located at the main library and branch libraries respectively. Various products such as bar-code labels and workstation furniture are also acquired. The construction of the computer room involves minor civil work, electrical installation and modifications to service ounters.